Theorizing, Measuring, and Predicting Knowledge Sharing Behavior in Organizations - a Social Capital Approach - WAH, Chay Yue (Institutional Knowledge at Singapore Management University, 2005)
This study aims to understand the social and organizational factors that influence knowledge sharing. A model of knowledge management and knowledge sharing was developed inspired by the work of Nahapiet and Ghoshal. Data on demographics and various social capital measures were collected from a sample of members of a tertiary educational institution in Singapore in 2003. Reward & recognition, open-mindedness and cost concerns of knowledge hoarding turned out to be the strongest predictors of knowledge sharing rather than pro-social motives or organizational concern. Overall, the findings provide evidence for the importance of a conducive organizational climate and state-of-the art performance management systems in high-performing knowledge organizations.